Pengaruh Intensitas Aset Tetap, Beban Pajak Tangguhan Dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak: Studi Empiris Pada Perusahaan Consumer Non-Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Sariningsih, Neneng; Enan Trivansyah (Perwira Journal of Economics & Business, 2024)
This study aims to prove empirically regarding the effect of fixed asset intensity, deferred tax expense and sales growth on tax avoidance. The population of this study is consumer non-cyclicals companies listed on the Indonesia Stock Exchange for 2017-2021. The sampling technique in this study was purposive sampling. So that the sample used was 36 companies with 5 years of observation. The research method used is a quantitative method using secondary data. The analysis technique used is panel data regression analysis with the Eviews 9 program by analyzing descriptive statistics, panel data regression model test, panel data regression model estimation, classical assumption test, panel data regression analysis, coefficient of determination, T statistical test and F statistical test. The results of this study indicate that partial fixed asset intensity has a significant effect on tax avoidance, partially deferred tax expense has no effect on tax avoidance, partially sales growth has a significant effect on tax avoidance. Simultaneously the intensity of fixed assets, deferred tax expense and sales growth affect tax avoidance.